Ecological Crisis: Seyyed Hossein Nasr’s Thought on Theophany - Muannas; Nasution, Muhammad Ali Azmi; Endang Ekowati (Yayasan Bayt Shufiya Nusantara, 2025)
The current global ecological crisis reflects not only material environmental degradation but also a profound spiritual crisis of modern humanity. This article aims to analyze the concept of theophany in the thought of Seyyed Hossein Nasr as a metaphysical foundation for establishing an ecological ethic rooted in Islamic spirituality. The study employs a philosophical-interpretative approach with a qualitative hermeneutic method, reviewing primary and secondary literature, including Nasr’s major works. Thematic and hermeneutic analyses reveal the ontological, epistemological, ethical, and socio-theological dimensions of theophanic perspectives on nature. Findings indicate that, for Nasr, all reality manifests God (theophany), making nature a reflection of the Divine presence that must be safeguarded with moral and spiritual responsibility. Modern ecological crises arise from the loss of theophanic awareness, leading to the exploitation of nature without recognition of its sacred dimension. Restoring human consciousness to a sacred cosmic order positions theophany as the foundation of ecological ethics that integrates faith, knowledge, and daily practices. This study underscores that addressing environmental crises requires not only technological or policy interventions but a spiritual revolution that affirms humanity’s cosmic relationship with God and creation. The article contributes to the development of contemporary Islamic ecological philosophy and offers a conceptual framework for environmentally responsible practices grounded in transcendent values.